Human hippocampal CA3 damage disrupts both recent and remote episodic memories - Miller, Thomas D; Chong, Trevor T-J; Aimola Davies, Anne M; Johnson, Michael R; Irani, Sarosh R; Husain, Masud; Ng, Tammy WC; Jacob, Saiju; Maddison, Paul; Kennard, Christopher; Gowland, Penny A; Rosenthal, Clive R (eLife, 2020)
Neocortical-hippocampal interactions support new episodic (event) memories, but there is conflicting evidence about the dependence of remote episodic memories on the hippocampus. In line with systems consolidation and computational theories of episodic memory, evidence from model organisms suggests that the cornu ammonis 3 (CA3) hippocampal subfield supports recent, but not remote, episodic retrieval. In this study, we demonstrated that recent and remote memories were susceptible to a loss of episodic detail in human participants with focal bilateral damage to CA3. Graph theoretic analyses of 7.0-Tesla resting-state fMRI data revealed that CA3 damage disrupted functional integration across the medial temporal lobe (MTL) subsystem of the default network. The loss of functional integration in MTL subsystem regions was predictive of autobiographical episodic retrieval performance. We conclude that human CA3 is necessary for the retrieval of episodic memories long after their initial acquisition and functional integration of the default network is important for autobiographical episodic memory performance.
Keywords: hippocampal subfields; retrograde amnesia; episodic memory; cornu ammonis; default network; LGI1-antibody limbic encephalitis